Impact of green policies, geopolitical risks, and imports on green production: formulating the SDG policies for G7 countries - Ahsan Anwar; Afshan Hamid; Magdalena Radulescu; Arshian Sharif (Environmental Sciences Europe)
Abstract In the modern era, sustainability is integrated with development. The industrial sector keeps pace with ecology and follows the path of modernization through innovations directly related to environmental sustainability. To preserve the environment in this fast-growing global economy, the existing literature identifies various socio-economic, macroeconomic, and institutional factors influencing environmental quality. However, the available studies largely ignore the influence of geopolitical risk, environmental policy stringency, and imports on green production practices. To bridge this void, this study aims to analyze the impact of geopolitical risk and environmental policy stringency on green production practices. In this regard, the panel of G7 countries has been chosen for the period from 1990 to 2020, as this intergovernmental and political and economic forum better suits our problem statement. To make empirical analysis extensively, the Panel Quantile Regression (PQR) technique has been applied, which has several advantages over the standard linear regression techniques of panel data analysis, particularly in dealing with outliers in the data set and heterogeneity across various quantiles of the dependent variable distribution. The empirical outcomes enunciate the adverse impact of geopolitical risk and imports on green production practices in G7 countries with a range of − 0.85 to − 0.042 and − 0.322 to − 0.191, respectively. Conversely, strict environmental policy has a constructive and meaningful impact on green production practices, following a range of 0.148 to 0.269. In the last section, considering the empirical outcomes, the study suggests relevant policy suggestions which also help G7 economies to secure several sustainable development goals (SDGs), such as SDG 9 (industrial and innovation), SDG 12 (responsible consumption and production), SDG 13 (climate change), SDG 16 (promoting peace, justice system, and strengthening institutions), and SDG 17 (partnerships for the common goals). Graphical Abstract